Inter-Satellite Radiometer Calibration of WindSat, TMI and SSMI - Gopalan, Kaushik; Jones, Linwood W.; Kasparis, Takis; Wilheit, Thomas T. (My University, 2008)
NASAs Global Precipitation Measurement (GPM) Mission will consist of a constellation of cooperative satellites with microwave radiometers to make global rainfall measurements. It is crucial that the brightness temperature (Tb) measurements from these satellite radiometers be consistent with each other. This may be achieved by the radiometric inter-comparison of near-simultaneous collocated oceanic measurements from pairs of satellites. In this paper, we describe two methods of performing such inter-comparisons. The first uses a radiative transfer model (RTM) to predict expected Tb differences between a pair of radiometer channels due to frequency and incidence angle differences, and then computes the unexplained relative radiometric bias between the channels over a wide variety of environmental conditions. The other approach uses a multi-variable linear regression built from RTM Tb simulations of all frequency channels for V and H polarizations. These two approaches are used to compare external measurements between the TRMM Microwave Imager (TMI), WindSat (on Coriolis), and SSMI (on DMSP F-13 and F-14).
Keywords: Computational modeling; Linear regression; Predictive models; Brightness temperature; Frequency; Satellite broadcasting; Microwave measurements; Sea measurements; Microwave radiometry; Calibration